Literature Review: Design Thinking for More Meaningful and Student-Centered Learning in Mathematics Education. - Muhammad Sobirin; Nidia Winda Sari; Sriayu Lestari; Wanda (Culture education and technology research (Cetera), 2025)
Meaningful and student-centered mathematics learning required innovative approaches to enhance students' conceptual understanding and engagement. One approach that was explored in this study was Design Thinking, which emphasized empathy, creative problem-solving, and iterative solutions. This study aimed to investigate how Design Thinking could be applied in mathematics learning to improve students' understanding while promoting more active and reflective learning experiences. A literature review and an analysis of Design Thinking implementation in mathematics classrooms were conducted. The findings reveal that incorporating Design Thinking in mathematics learning increases student engagement, fosters creativity in problem-solving, and enhances conceptual understanding.